Questioning the Challenge to Screen Use Guidelines - Catherine L'ecuyer; José Víctor Oron Semper; Irene Montiel; Alfonso Osorio; Jesús López-Fidalgo; M. Angustias Salmerón Ruiz (Teoría de la Educación: Revista Interuniversitaria)
In September 2023, “An umbrella review of the benefits and risks associated with youths’ interactions with electronic screens” was published in Nature. This review aimed at understanding the influence of electronic screens on the health and educational outcome of children and adolescents from 0-18 years old. The authors concluded that current screen use guidelines may be too simplistic, that they mischaracterize the strength of the evidence or do not acknowledge the important nuances of the issue. As a result, they supported the trend of moving away from recommendations to reduce screen use and instead focus on the type of screen use. Our contribution focuses on answering the question of whether the results of this review are sufficient to challenge current screen use guidelines. To do so, we explain the current literature on screen use guidelines that the review generically referred to as well as the rationale behind them, and then we proceed to explain why the review’s findings are insufficient to challenge these guidelines. We demonstrate that some of the review's main conclusions are not consistent with its own findings and that they fail to explain the relationship between their findings and the discreditation of current guidelines. Absence of evidence is not evidence of absence and investigators should be careful in questioning public health recommendations based on incomplete evidence.